Nuprl Lemma : in-simple-loc-comb-1-concat
∀[Info,A,B:Type]. ∀[f:Id ─→ A ─→ bag(B)]. ∀[X:EClass(A)]. ∀[es:EO+(Info)]. ∀[e:E].
  (Singlevalued(X) 
⇒ (∀i:Id. ∀a:A.  (#(f i a) ≤ 1)) 
⇒ e ∈b f@(Loc, X) = e ∈b X ∧b (¬bbag-null(f loc(e) X(e))))
Proof
Definitions occuring in Statement : 
concat-lifting-loc-1: f@
, 
simple-loc-comb-1: F(Loc, X)
, 
sv-class: Singlevalued(X)
, 
eclass-val: X(e)
, 
in-eclass: e ∈b X
, 
eclass: EClass(A[eo; e])
, 
event-ordering+: EO+(Info)
, 
es-loc: loc(e)
, 
es-E: E
, 
Id: Id
, 
band: p ∧b q
, 
bnot: ¬bb
, 
bool: 𝔹
, 
uall: ∀[x:A]. B[x]
, 
le: A ≤ B
, 
all: ∀x:A. B[x]
, 
implies: P 
⇒ Q
, 
apply: f a
, 
function: x:A ─→ B[x]
, 
natural_number: $n
, 
universe: Type
, 
equal: s = t ∈ T
, 
bag-size: #(bs)
, 
bag-null: bag-null(bs)
, 
bag: bag(T)
Lemmas : 
all_wf, 
Id_wf, 
le_wf, 
bag-size_wf, 
nat_wf, 
sv-class_wf, 
es-E_wf, 
event-ordering+_subtype, 
event-ordering+_wf, 
eclass_wf, 
bag_wf, 
eq_int_wf, 
bool_wf, 
eqtt_to_assert, 
assert_of_eq_int, 
eqff_to_assert, 
equal_wf, 
bool_cases_sqequal, 
subtype_base_sq, 
bool_subtype_base, 
assert-bnot, 
neg_assert_of_eq_int, 
nequal-le-implies, 
equal-wf-base-T, 
bag-size-one, 
bag-combine-single-left, 
single-bag_wf, 
es-loc_wf, 
eclass-val_wf, 
bag-union-single, 
bag-subtype-list, 
null-bag-size, 
iff_imp_equal_bool, 
bnot_wf, 
equal-wf-T-base, 
not_wf, 
assert_wf, 
iff_wf, 
iff_transitivity, 
iff_weakening_uiff, 
assert_of_bnot, 
bag-size-zero, 
decidable__le, 
false_wf, 
not-le-2, 
condition-implies-le, 
minus-add, 
minus-one-mul, 
add-swap, 
add-associates, 
zero-add, 
add-commutes, 
minus-zero, 
add_functionality_wrt_le, 
le-add-cancel2, 
bag_combine_empty_lemma, 
bag_union_empty_lemma, 
bag_size_empty_lemma, 
bfalse_wf
Latex:
\mforall{}[Info,A,B:Type].  \mforall{}[f:Id  {}\mrightarrow{}  A  {}\mrightarrow{}  bag(B)].  \mforall{}[X:EClass(A)].  \mforall{}[es:EO+(Info)].  \mforall{}[e:E].
    (Singlevalued(X)
    {}\mRightarrow{}  (\mforall{}i:Id.  \mforall{}a:A.    (\#(f  i  a)  \mleq{}  1))
    {}\mRightarrow{}  e  \mmember{}\msubb{}  f@(Loc,  X)  =  e  \mmember{}\msubb{}  X  \mwedge{}\msubb{}  (\mneg{}\msubb{}bag-null(f  loc(e)  X(e))))
Date html generated:
2015_07_23-AM-11_29_39
Last ObjectModification:
2015_01_28-PM-11_16_55
Home
Index